The moderating role of business environment in the relationship between entrepreneurial orientation and business performance among Nigerian SMEs - Aliyu Mukhtar Shehu; Rosli Mahmood (Penerbit Universiti Kebangsaan Malaysia, 2015)
Small and medium enterprises (SMEs) are essential to economic growth of Nigeria, and therefore are considered as a major source of job creation, and poverty reduction as they signifi cantly contribute to the gross domestic products. Thus the aim of this study is to investigate the direct relationship between entrepreneurial orientation (EO) and business performance of SMEs in Nigeria, with the moderating effect of business environment. A quantitative research design was employed, using a structured questionnaire survey, and a total of 511 valid responses were duly completed and returned, representing 79.8 percent response rate. Based on theoretical consideration, a framework was developed to investigate these relationships. The result of regression analysis established a strong and positive relationship between EO and business performance. However, the hypothesized moderating effect of the business environment on the relationship between EO and business performance was not supported. The fi ndings from this study will benefi t SME owner/managers, regulatory agencies, and government at all levels, and will also serve as a frame of reference for future studies.